2016
DOI: 10.1590/0034-737x201663050006
|View full text |Cite
|
Sign up to set email alerts
|

Influência do sistema de colheita nas características da fibra do algodão

Abstract: RESUMO Escolhas no manejo cultural, como a do cultivar e a do sistema de colheita, podem influenciar os índices dos parâmetros de qualidade da fibra do algodão. Objetivou-se, com este trabalho, analisar as características das fibras de dois cultivares de algodão submetidos a diferentes sistemas mecanizados de colheita (picker e stripper). O experimento foi conduzido na safra de 2012, com espaçamento de 0,45 m entre linhas, no município de Juscimeira, MT. Utilizou-se delineamento em blocos casualizados, em esqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…O planejamento da semeadura do algodão deve ser realizo para que a colheita seja feita em uma época favorável com poucas precipitações (junho e julho), para que não afete o preço da pluma, que segundo Kazama et al (2016), a colheita é uma etapa de alto custo e de extrema importância no processo produtivo do algodão, uma vez que, se mal conduzida, acarretará prejuízos de qualidade e de quantidade ao produto final.…”
Section: Resultsunclassified
“…O planejamento da semeadura do algodão deve ser realizo para que a colheita seja feita em uma época favorável com poucas precipitações (junho e julho), para que não afete o preço da pluma, que segundo Kazama et al (2016), a colheita é uma etapa de alto custo e de extrema importância no processo produtivo do algodão, uma vez que, se mal conduzida, acarretará prejuízos de qualidade e de quantidade ao produto final.…”
Section: Resultsunclassified
“…These factors include environmental growth conditions, extraction methods, harvesting timing, and harvesting methods [142]. Plant age, harvesting method, and fiber extraction method are crucial in determining fiber quality and, consequently, the quality of composites produced with these fibers.…”
Section: Characteristics and Properties Of Natural Lignocellulosic Fi...mentioning
confidence: 99%
“…The planting system adopted in the farms is SPD, possibly inserted in the area volume cited by Peixoto et al (2019), whose understanding is anchored in the molds proposed by Phillips et al (1980), presenting the gains gauged by Salton, Hernani and Fontes (1998). Cotton planting in the research region is done in the conventional system (Clawson et al, 2008) to the detriment of the adensed system as discussed in Rosolem et al (2012) and Kazama et al (2016). According to the APPA executive, "our region is very humid, so if it is adensed, it is much more prone to diseases.…”
Section: Fig4: Appa's Activities In the Various Stages Of Cotton Productionmentioning
confidence: 99%
“…The technology of reducing the spacing between the rows of cotton -adensed method (Narrow Row cotton -NRC), is a technique of North American origin that allows reducing the crop cycle (Rosolem et al, 2012;Kazama et al, 2016), allowing the minimization of phytosanitary applications, with consequent reduction of production cost, being, in many cases more advantageous in relation to the conventional cropping system (Conventional Row)spacing between 0.76 to 102 cm (Constable, 1977;Clawson et al, 2008). Empirical studies have demonstrated the reduction in costs resulting from the adoption of the adensed planting system in comparison with the conventional system (Jost & Cothren, 2001), above all because of the lower use of phytosanitary products.…”
Section: Introductionmentioning
confidence: 99%